The central bank between the lender and the last medic - فلحي, هيفاء مزهر (Journal of Legal Sciences, 2019)
The central bank is the financial director of the economic system of all countries of the world, which is considered the main official of the monetary and monetary policy in it and seeks to control the offer of money and its value in the issuance of currencies and the setting of interest rates, and this role is essential for both money and credit, The main artery of modern economic systems. If money and credit rise very quickly, commercial companies may not be able to meet the requirements of increased production.     Thus, central banks perform similar functions throughout the world today with the aim of achieving the public good, but the exercise of these functions varies from one economic environment to another.